Analisis Variasi Nilai Duty Cycle pada PWM Terhadap Durasi Pengisian Baterai Lithium-Ion dan Lithium-Polymer - Febriansyah Kumaraning Akbar; Fatkhur Rohman (JASIEK (Jurnal Aplikasi Sains, Informasi, Elektronika dan Komputer), 2020)
Lithium batteries are currently widely used as energy storage devices in electric vehicles. However, it takes quite a long time to charge the battery. One solution to the problem of battery charging is to increase the charging voltage and current. The purpose of this study was to determine the effect of variation in the value of the duty cycle with pulse-width modulation on the duration of the battery charge. The battery charging test method uses various duty cycle values ranging from 50% to 100%. Data extraction uses a method of changing the output voltage and current with different duty cycle values on a pulse width modulation signal, which is controlled by the Arduino Uno microcontroller. The results of this study show that changes in the duty cycle value can affect the charging time of Lithium Ion and Lithium Polymer batteries. Fastest charging results on Lithium Ion battery 15,183 minutes with 100% duty cycle at 14V output voltage and 5.83A Lithium polymer battery 15,083 minutes with 100% duty cycle at 14V output voltage and current 6 ,14A.